2016
DOI: 10.1166/jctn.2016.4816
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Microporous Silica Material (mcm-41) on Graphene Sheet as a Nano-Carrier

Abstract: In this work, we have investigated the MCM-41 (M41) adsorbed on the graphene sheet noncovalently and covalently using B3LYP/6-31G * and M05-2X/6-31G * * levels at different distances. The nuclear magnetic resonance (NMR) of 1 H and 13 C, 17 O and 29 Si has calculated by gauge independent atomic orbital (GIAO) method for M41G at 1.8, 2 and 2.3 Å. A study on the electronic properties, such as HOMO and LUMO energies, natural bond-orbital (NBO) analysis and properties structure, ChelpG have been performed by DFT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Nuropharmacokinetic studies confirmed that the brain uptake clearance of the rivastigmine-loaded MSNs was significantly higher than the free drug . This study highlighted the importance of surface functionalization of MSNs to enable them to function as effective drug carriers for delivery to the brain. , In the same year, angiopep-2 modified lipid-coated MSNs were introduced for glioma treatment. The therapeutic efficacy of the brain-targetng NPs on intracranial C6 glioma-bearing rats was high …”
Section: Introductionmentioning
confidence: 71%
“…Nuropharmacokinetic studies confirmed that the brain uptake clearance of the rivastigmine-loaded MSNs was significantly higher than the free drug . This study highlighted the importance of surface functionalization of MSNs to enable them to function as effective drug carriers for delivery to the brain. , In the same year, angiopep-2 modified lipid-coated MSNs were introduced for glioma treatment. The therapeutic efficacy of the brain-targetng NPs on intracranial C6 glioma-bearing rats was high …”
Section: Introductionmentioning
confidence: 71%
“…(13) for spin-polarized system and closeshell system are defined in the same way as in ELF 43 . This work has been studied based some previous works 44- 167 and has compared with the experimental data. The ab-initio and DFT methods are used for the model system of the ONIOM layers and the semi empirical methods of pm3mm (including pseudo=lanl2) and Pm6 are used for the medium and low layers, respectively.…”
Section: Electron Localization Function (Elf)mentioning
confidence: 99%
“…27 These types of compounds can be employed for the production of solid spherical nanoparticles, vesicular polymersomes, micelles, polymer–drug conjugates, polyplexes, and dendrimers. 28 Cur is a polyphenolic compound extracted from the rhizomes of Curcuma longa 29 and is widely used in complementary medicine, as it possesses much biological activity, including analgesic, antioxidant, anti-inflammatory, and antiseptic properties. A large body of evidence shows that Cur has anti-neoplastic activity, and it plays a significant role in regulating the oncogene expression, cell cycle suppression, stimulating the apoptosis process, and preventing tumorigenesis and metastasis.…”
Section: Introductionmentioning
confidence: 99%